Sports infrastructure in Ukraine during war and post-war reconstruction: Analysis, challenges, and modernisation mechanisms - Hrynchenko, Ihor; Sobko, Iryna; Kyrpenko, Vitalii; Palevych, Serhii (Educational Challenges, 2025)
Purpose. This study aims to develop viable strategies for the revival and modernisation of Ukraine’s sports infrastructure in the context of post-war reconstruction.Methodology. A large amount of data was processed using methods of systematisation, comparative analysis and synthesis, including scientific publications, analytical reports (notably from the Kyiv School of Economics and the Ministry of Youth and Sports of Ukraine), as well as regulatory and legal documents. A comparative analysis of quantitative data on damage caused and qualitative assessments of systemic problems was conducted. Additionally, the results of expert studies conducted using the Delphi method were considered, enabling the identification of critical needs and priority areas for industry development.Results. It was established that large-scale military aggression caused extensive destruction of the Ukrainian sports infrastructure, resulting in consequences that extend beyond material losses. The analysis shows that the war exacerbated and intensified systemic shortcomings that existed long before February 2022, particularly uneven development, an outdated material and technical base, and a lack of clear state policy. The loss of infrastructure has led to a decline in physical activity, the depletion of human resources and the mass migration of athletes and coaches. It has been demonstrated that rebuilding outdated facilities alone is insufficient and will only perpetuate existing issues.Conclusions. A true revival of the sports industry requires a fundamental transformation that includes systemic reforms, the diversification of funding sources (through international aid, public–private partnerships, and private investment), and innovative approaches. This includes creating multifunctional, energy-efficient and inclusive facilities that meet society’s modern needs. Investment in sport should be viewed as a strategic, long-term investment in human capital, psychological rehabilitation, and the restoration of national spirit.
Keywords: sports infrastructure; military aggression; restoration; modernisation; Ukraine